2011
DOI: 10.1128/aem.05130-11
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Rumen Methanogen Populations of Lactating Jersey and Holstein Dairy Cows under the Same Diet Regimen

Abstract: In the dairy cattle industry, Holstein and Jersey are the breeds most commonly used for production. They differ in performance by various traits, such as body size, milk production, and milk composition. With increased concerns about the impact of agriculture on climate change, potential differences in other traits, such as methane emission, also need to be characterized further. Since methane is produced in the rumen by methanogenic archaea, we investigated whether the population structure of methanogen commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
75
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 33 publications
13
75
0
2
Order By: Relevance
“…The nature and representation of methanogens from the Skillman et al (2006) study show significant overlap with that of the Holsteins analyzed by Whitford et al (2001) presented above. In a recent report by King et al (2011), the frequency of M. ruminantium (33.3%) and unassigned St-Pierre and Wright Methanobrevibacter species (28.6%) in Jersey cows from a mixed herd were also found to be similar to the study by Skillman et al (2006), but in contrast M. millerae was identified as a prominent methanogen (34.6%) and unassigned species of Methanosphaera were observed at a much lower frequency.…”
Section: Dairy Cattlesupporting
confidence: 60%
See 1 more Smart Citation
“…The nature and representation of methanogens from the Skillman et al (2006) study show significant overlap with that of the Holsteins analyzed by Whitford et al (2001) presented above. In a recent report by King et al (2011), the frequency of M. ruminantium (33.3%) and unassigned St-Pierre and Wright Methanobrevibacter species (28.6%) in Jersey cows from a mixed herd were also found to be similar to the study by Skillman et al (2006), but in contrast M. millerae was identified as a prominent methanogen (34.6%) and unassigned species of Methanosphaera were observed at a much lower frequency.…”
Section: Dairy Cattlesupporting
confidence: 60%
“…Recently, rumen methanogens were investigated in lactating Holsteins from a mixed dairy herd (i.e. Holsteins and Jerseys) maintained under a TMR consisting of 33% forage, 33% corn silage and 33% concentrate (King et al, 2011), and although Methanobrevibacter was found to be the most prominent genus the population structure consisted of unassigned Methanobrevibacter species (47.8%), M. ruminantium (28.3%) and Methanobrevibacter millerae (16.7%). In another study, Hook et al (2011) studied the effects of changing the diet of non-lactating Holsteins from hay to a hay and mixed grain regimen.…”
Section: Dairy Cattlementioning
confidence: 99%
“…Other data demonstrated predominance of only M. ruminantium (Leahy et al, 2010), whereas other data indicated the order Methanobacteriales as predominant in the rumen (Jarvis et al, 2000). However, the literature is still expanding and newer methanogens are being identified (Wright et al, 2008;Zhou et al, 2009;King et al, 2011;Lee et al, 2013).…”
Section: Characteristics Of the Rumen Ecosystem In Relation To Methanmentioning
confidence: 92%
“…However, Impala-3 was the only individual with no sequence reads in OTU 7 (Table 3). Furthermore, the Methanobrevibacter smithiigottschalkii-millerae-thaueri (SGMT) clade composed 81 % of the sequence reads from OTUs 1-8 while the Methanobrevibacter ruminantium-olleyae (RO) clade accounted for just 2 % [24]. …”
Section: Analysis Of Rumen Methanogensmentioning
confidence: 99%